EFFECT OF SUPPLEMENTATION OF OREGANO (ORIGANUM VULGARE) ESSENTIAL OIL WITH PROBIOTICS ON ECONOMICS AND GROWTH PERFORMANCE OF BROILER CHICKENS - HARSHAL NILKANTH REWATKAR; VIPIN; KUNDAN KUMAR; PRAMOD KUMAR SONI; JAI PRAKASH (The Bioscan, 2020)
This study was conducted to evaluate the efficacy of oregano essential oil (OEO) (Origanum vulgare L.) individually or in combination with probiotics as a dietary supplement in broiler chicken for 42 days. A total of 240 straight run “Ven-Cobb 400Y” strain commercial day-old broiler chicks were randomly assigned to 4 treatments with 4 replications each (15 birds per replicate): T0 (standard broiler diet as per BIS, 2007), T1 (Standard broiler chicken diet as per BIS, 2007 + oregano essential oil @ 0.15 gm/kg diet) T2 (Standard broiler chicken diet as per BIS, 2007+ probiotic (encapsulated Saccharomyces cerevisiae) @ 200 gm/tones) T3 (Standard broiler chicken diet as per BIS, 2007 + oregano essential oil @ 0.15 gm/kg diet + probiotic (encapsulated Saccharomyces cerevisiae) @ 200 gm/tones). Improved Cumulative body weight gain and feed efficiency (P<.05) were found in (T3) being 1163.96 gm and 1.22 respectively, followed by (T2) having 1128.18 gm and 1.22 while (T1) 1106.83 gm and 1.29 and T0 (control) 1063.1 gm and1.32. It can be concluded that oregano oil at the levels of 0.15 gm/kg when fed along with probiotics (Saccharomyces cerevisiae) appears as a promising alternative to antibiotic growth promoters for augmented performance in broiler chickens.